SIGNIFICANT DIFFERENCES BETWEEN UZBEKISTAN AND THE CIS COUNTRIES IN THE FIELD OF FINANCIAL REPORTING. - Yakubjonov D.R.; Mansuralieva K. R.; Rakhimov H.K. (Ta’lim innovatsiyasi va integratsiyasi, 2024)
Abstract: The article summarizes the experience of foreign countries in accounting for financial results of organizations, including the features of accounting systems in Russia, Ukraine and Kazakhstan. From this analysis, it was concluded that the convergence of national accounting systems under IFRS in the CIS countries. The article also described the main approaches to the analysis of financial results used in the CIS countries.